2002
DOI: 10.1097/00000658-200212000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental and Distinct Roles of P-Selectin and LFA-1 in Ischemia/Reperfusion-Induced Leukocyte-Endothelium Interactions in the Mouse Colon

Abstract: This study provides evidence that leukocyte rolling is exclusively and nonredundantly mediated by P-selectin and that firm adhesion is supported by LFA-1 in I/R-induced leukocyte recruitment in the colon. Taken together, both P-selectin and LFA-1 may be important targets to control pathologic inflammation in I/R-induced tissue injury in the colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 44 publications
7
38
1
4
Order By: Relevance
“…Thus, it was found that inhibition of P-selectin, but not E-selectin reduced reperfusion-induced leukocyte rolling and adhesion in the colon, which is in agreement with previous fi ndings [29]. Nonetheless, we observed, herein, that inhibition of PSGL-1 decreased leukocyte rolling by nearly 90 % in colonic I/R.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, it was found that inhibition of P-selectin, but not E-selectin reduced reperfusion-induced leukocyte rolling and adhesion in the colon, which is in agreement with previous fi ndings [29]. Nonetheless, we observed, herein, that inhibition of PSGL-1 decreased leukocyte rolling by nearly 90 % in colonic I/R.…”
Section: Discussionsupporting
confidence: 93%
“…Histones have been reported to bind and activate TLR2, TLR4 and TLR9 on immune cells [10,34,35], whereas others have shown that histones mainly cause toxic effects on different cell types, such as endothelial and epithelial cells [3,4]. Nonetheless, histone-dependent inflammatory reactions are frequently associated with increased tissue accumulation of leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular histones have also been shown to increase thrombin generation, which could cause dysfunctional coagulation in systemic inflammation [6]. In this context, it is important to note that leukocyte recruitment is a rate-limiting step in mediating tissue damage in many inflammatory diseases, including sepsis, acute pancreatitis [7] and colitis [8] as well as cholestatic liver injury [9] and ischemia reperfusion [10]. Interestingly, inhibition of histone function has been associated with reduced levels of tissue accumulation of leukocytes in disease models, such as endotoxemia and acute kidney injury [5,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, numerous studies have shown that P-, E-, and L-selectin support early interactions between leukocytes and endothelial cells at sites of inflammation (13,19,21,28). Selectins bind to complex carbohydrates expressed on specific glycoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, neutrophil stiffness increases, promoting mechanical sequestration of neutrophils in lung capillaries (20,34). It is widely held that leukocyte rolling is mediated by the selectin family of adhesion molecules, including P-, E-and L-selectins although their relative roles appear to be both tissue-and stimulus-dependent (2,28). Selectin ligands are complex glycoproteins and, in terms of selectin specificity and function, are poorly understood.…”
mentioning
confidence: 99%